PENGARUH PENGETAHUAN INVESTASI, MOTIVASI INVESTASI, DAN LITERASI KEUANGAN TERHADAP MINAT INVESTASI MAHASISWA - Masya, Masya'il Abidah; Wulan Suryandani (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The aim of the research carried out was to determine the influence of investment knowledge, invesment motivation and financial literacy on the investment interest of YPPI Rembang University Management Study Program student in the capital market. The research population was students of the YPPI Rembang University Management Study Program. Sampling Using propotional random sampling sample of 70 respondents. Data analysis used multiple liniear regression with SPPS 24.0. The research results show that the investment motivation and finacial literacy variables have a positive effect on students’ invesment intentions, while the investment knowledge variables has a positive effect on students’ invesment intentions, but has no significant. The Adjusted R value shows a value of 0,583. This means that the three independent variables, namely investment knowledge, investment motivation and financial literacy, are only able to explain 58,3%, of investment, while 41,7% can be explained by variables out side this.